Plotting Directionality on Positional Maps: A Methodological Consideration for Situational Analysis. Issue 1 (7th June 2019) - Meszaros, Megan; Meyer, Desneige; Vold, Lindsey; Martin, Wanda
In this article, we aim to expand situational analysis (SA), oriented by complex adaptive systems (CAS), by adding the dimension of directionality over time to positional maps. This addition furthers the analytic utility of SA and can aid researchers in identifying areas for transformative action regarding social justice and health equity issues. Adding directionality over time to positional maps pushes researchers to explore how positions move, evolve, and how they could continue to develop. Analyzing these elements expands the analytic utility of positional maps as researchers abductively analyze explicit connections between theorized antecedents, current conditions, and potential futures within a CAS to understand positional movements. The purpose of this analysis is not as a predictive tool but as a tool in identifying potential actionable areas for interventions while further grounding SA in its Foucauldian and Straussian theoretical roots. We use an ongoing public health project in the Ngorongoro Conservation Area, Tanzania, to demonstrate how a researcher can apply directionality over time to positional maps.